Treatment of Chronic Bony Mallet Fingers by Dorsal Extension Block Pinning with Percutaneous Curettage - Fumiaki Takase; Kyoko Yamasaki; Takeshi Kokubu; Yutaka Mifune; Atsuyuki Inui; Ryosuke Kuroda (Case Reports in Orthopedics)
Dorsal extension block pinning is a commonly performed surgical technique for acute bony mallet fingers. However, the treatment of chronic bony mallet finger remains controversial. We investigated the use of dorsal extension block pinning with percutaneous curettage for chronic bony mallet fingers. Seven patients with chronic bony mallet fingers were treated by dorsal extension block pinning with percutaneous curettage. The average age was 17 (range, 12–23) years, and the average time from injury to surgery was 20 (range, 7–49) weeks. Bone union was achieved in all patients. None of the patients experienced pain after bone union. The average loss of distal interphalangeal joint extension was 6 (range, 5–20) degrees, and the average flexion was 59 (range, 40–80) degrees. The Crawford functional score was excellent in three patients, good in two, and fair in two. Dorsal extension block pinning with percutaneous curettage could be a useful treatment for chronic bony mallet fingers.